Analisis Pengaruh Pelatihan Soft Skills, Kepemimpinan Adaptif, dan Budaya Belajar Terhadap Kinerja Individu di Era Digital pada Industri Manufaktur di Cikarang - Ismi Zuliyanti; Lasron Saputra Lumbanraja; Dea Amanda (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2024)
This study investigates the influence of soft skills training, adaptive leadership, and learning culture on individual performance in the digital era, specifically within the manufacturing industry in Cikarang. Utilizing a quantitative research method, data was collected through a questionnaire distributed to 100 respondents. The analysis, conducted using multiple linear regression, reveals that both soft skills training and adaptive leadership significantly enhance individual performance, while a supportive learning culture also plays a crucial role in this improvement. The findings underscore the importance of fostering a learning culture within organizations, as it encourages continuous learning and skill development among employees . This research offers valuable insights for human resource management, suggesting that effective training programs should be designed to boost employee performance. The study advocates for companies to invest in soft skills training and cultivate adaptive leadership and a robust learning culture as strategic approaches to enhance workforce performance in the digital era.